The effect of high intensity interval swimming training on Glial cell line-derived neurotrophic factor and Rearranged during transfection (RET) gene expression in hippocampal tissue in rats with reserpine induced-Parkinson's disease - Sahar Abdolahi; Mehrzad Moghadasi; Mohammdamin Edalatmanesh; Sara Hojati (Shahid Beheshti University, 2024)
Background and Purpose: Parkinson's disease is a progressive neurological disorder, where loss of dopamine neurons in the substantia nigra and dopamine depletion in the striatum cause characteristic motor and nonmotor symptoms. Glial cell line-derived neurotrophic factor (GDNF) is one of the most important neurotrophins that regenerates dopaminergic neurons by Rearranged during transfection (RET) receptor tyrosine kinase in Parkinson's disease. The effect of exercise on these proteins are not well known. Therefore, the present study was conducted to examine the effect of high intensity swimming training on GDNF and RET gene expression in hippocampal tissue in rats with Parkinson's disease. Material and Methods: In this experimental and pure study, twenty-one male Wistar rats (age 8 to 10 weeks and weight 200-250 gr) were purchased from the Animal Breeding Center of Islamic Azad University, Shiraz branch and transferred to the animal laboratory of this university. Parkinson's disease was induced in fourteen rats by injection of 1 mg/kg reserpine during 5 days. Thereafter, they were randomly divided into Parkinson's disease group or Parkinson's disease + training group. The rats in the training group performed 6 weeks of high intensity interval swimming including 20 repetitions of 30 seconds swimming followed by 30 seconds rest. Moreover, seven remaining rats received no intervention and were allocated into the healthy control group. GDNF and RET gene expressions were measured in hippocampus 48h after the last training session, using Real Time-PCR. Data were analyzed by using one-way ANOVA test and Bonferoni's post-hoc. Data were analyzed by using SPSS22 at the P<0.05. Results: Data analyzes revealed that GDNF and RET gene expression were reduced after induction of Parkinson's disease compared to the healthy control group (P=0.001, P=0.03, respectively).After 6 weeks of training, GDNF and RET gene expressions were increased compared to the Parkinson's disease group (P=0.009, and P=0.007, respectively), whereas, no significant differences were observed between training group and healthy control group (P=0.6 and P=0.9. respectively). Conclusion: In general, it seems that high-intensity interval swimming training used in this study could improve dopaminergic neuron survival in Parkinson's disease by increasing GDNF as a neurotrophine factor and subsequent signaling receptor tyrosine kinase RET. Since, the available data are scars in this field, future studies specially in human are needed.